Analisis Rasio Biaya Langsung dan Biaya Tidak Langsung Operasional Perguruan Tinggi X - Aminda, Renea Shinta; Purnahayu, Indu; Taryani, Heni (Jurnal Manajemen, 2020)
Higher education operational costs have a standard reference set in the standard unit of higher education operational costs, so it is hoped that there will be conformity and optimality and operational allocation of State Universities, therefore the purpose of this research is to analyze and examine in depth the ratio of direct and indirect costs. higher education operations, which use data from 2017 and 2018 because they meet the requirements for using the SSBOPT reference, using descriptive analysis techniques, content analysis and descriptive analysis. Sekaran & Bougie (2010) say content analysis is used to systematically analyze and identify information obtained from recorded interviews, advertisements, websites, and the like, then a description of the explanatory analysis obtained by the results of research in 2017, the amount of direct costs is 79, 24% while the indirect costs were 20.76%, then in 2018 the amount of direct costs was 71.86% while indirect costs were 28.14%. However, if the analysis is carried out one by one on the work unit, almost all work units, both faculties and departments, make expenditures that are not in accordance with the SSBOPT regulations, it is clearly stated in SSBOPT that the indirect costs of operating education are 50% of the direct costs of operating education. However, after adding spending data from the Directorate of Human Resources in the form of spending data on accounts 51 and 54 which are direct educational operational costs in general for institutions, the ratio of direct costs to indirect costs is in accordance with SSBOPT